2020
DOI: 10.1002/nano.202000051
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of graphene polyindole nanocomposite for enhanced corrosion protection of aqueous coating in 3.5% NaCl solution for low carbon steel

Abstract: Graphene polyindole (Gr@PIn) nanocomposite with varying content of graphene was synthesized via an in‐situ redox polymerization doping technique. The techniques like FT‐IR, XRD, SEM, and TEM were utilized to characterize the produced nanocomposites. The produced nanocomposites were cast on LCS (low carbon steel) substrate employing NMP as a solvent, 10% epoxy as a binder, and triethylenetetramine as a curing agent. The anti‐corrosion ability of the Gr@PIn nanocomposite coatings was established by performing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…rGO was synthesized by the oxidation of graphite powder according to the Hummers modified method, as described in our previous paper. 31 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…rGO was synthesized by the oxidation of graphite powder according to the Hummers modified method, as described in our previous paper. 31 …”
Section: Methodsmentioning
confidence: 99%
“…The order of positive shift in OCP of coated steel is as follows: PTh-TiO 2 -rGO > PTh-TiO 2 > PTh. The more positive shift in the values of OCP indicates their high corrosion resistance, which is a result of both barrier existence and the passive oxide layer effect at the coating interface. The presence of rGO and TiO 2 in the PTh-TiO 2 -rGO nanocomposite coating has shifted the potential in a more noble direction and improved the coating’s redox behavior and barrier characteristics . The higher corrosion protection ability of the PTh-TiO 2 -rGO and PTh-TiO 2 nanocomposite coatings over PTh for the full immersion time is due to a superior barrier effect, i.e., changes caused by the formation of a more adhesive, dense, and uniform layer on the steel surface.…”
Section: Corrosion Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyindole (PIN), a rising conducting polymer, is being explored and developed as a possible candidate for electrochromic devices 33,34 , sensors 35,36 , photocatalysis 37,38 , and electrocatalysis 39 , anticorrosion 40,41 , diodes 42,43 , supercapacitors 44,45 , batteries, and biology-related applications [45][46][47] . The studies on PIN has been started as early as 1976, Youmans, H. L et.al synthesised polyindole from indole through chemical polymerization 48 .…”
Section: Polyindole (Pin)mentioning
confidence: 99%
“…Several studies on polyindole revealed that they could be used as promising candidates for applications such as supercapacitors, batteries, electrochromic devices, sensors, electrocatalysis, catalysis, and anticorrosion. 77–83 Graphene and silver nanoparticles loaded polyindole have been subjected to electro activity studies and found that such system can be used as an electrode material for various applications. 84…”
Section: Conducting Polymer Nanocomposites As Biomedical Agentsmentioning
confidence: 99%